Atherosclerosis index and BMI: new predictors of cognitive function in ischemic survivors - Zhao, Lingyan; Qin, Chenyang; Yu, Hanbo; Zhang, Luofan; Zhang, Dingchen; Wang, Shu; Li, Guiping (Frontiers in Nutrition, 2025)
BackgroundThe atherogenic index of plasma (AIP) is a reliable surrogate marker for insulin resistance and is strongly associated with both stroke risk and prognosis. However, the associations of AIP and the composite index AIP-BMI with cognitive function among patients with ischemic stroke remain insufficiently studied.MethodsThis cross-sectional study included 2,933 patients with ischemic stroke. Demographic and clinical data were collected from all participants. The AIP was calculated as log [TG (mmol/L)/HDL-C (mmol/L)], and cognitive function was evaluated using the Mini-Mental State Examination (MMSE). Multivariable linear regression models were applied to examine the associations between AIP (and AIP-BMI) and MMSE scores, adjusting for potential confounders. Stratified and sensitivity analyses were further conducted to evaluate the robustness of the findings.ResultsThe mean age of participants was 64.8 years (SD 10.2), and 2,009 (68.5%) were male. Each one-unit increase in AIP was associated with a 1.15-point reduction in MMSE score (p < 0.001). Similarly, each one-unit increase in AIP-BMI corresponded to a 0.04-point decrease in MMSE score (p < 0.001). The inverse associations remained consistent when AIP and AIP-BMI were analyzed by tertiles.ConclusionHigher levels of AIP and AIP-BMI are independently associated with poorer cognitive performance in patients with ischemic stroke. These findings suggest that dyslipidemia-related metabolic disturbances may contribute to post-stroke cognitive impairment.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=120858, identifier ChiCTR2100042721.